Beyond the crisis: Role and effects of corporate social responsibility during the COVID-19 Pandemic - Iveta Ubreziova; Karol Čarnogurský; Mária Janošková (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article addresses the research gap in understanding corporate social responsibility (CSR) dynamics during the COVID-19 pandemic, presenting the outcomes of a national research initiative in Slovakia. Research Design & Methods: The research delves into the social, economic, and environmental components of CSR, aiming to quantify their individual effects and uncover potential interconnections. Operationalising questions into variables allows for a rigorous examination of these dimensions, utilizing factor analysis with principal component analysis. With 190 organisations answering a questionnaire, the study provides quantitative and qualitative insights. Findings: The results show that CSR has the most significant impact on strengthening corporate reputation across all three dimensions. CSR reinforced the importance of ethical and sustainable strategies during the pandemic, with organisations with an active CSR strategy performing better. The research confirmed that CSR is key to building corporate credibility and competitiveness. Implications & Recommendations: Based on the information above and the article's content, we want to provide direction for further research. It is mainly about investigating the impact of the COVID-19 pandemic, especially after the post-COVID-19 period, in the most critical areas that evoke CSR and the business environment, such as corporate culture, human resources, and companies' financial and economic situations. Contribution & Value Added: The presented research aimed to expand knowledge about the effects and impacts of social responsibility on organisations that implement socially responsible activities and the region and society in which they operate. We based the research on the processing of data from a nationwide survey. We processed a total of 190 valid questionnaires, which enabled the use of descriptive and inference statistics procedures.
Keywords: M14; O18; 330; corporate social responsibility; enterprises; quantitative analysis; pandemic; resilience strategies; sustainability